Stewart Bluefarb syndrome: case report of a rare variant of acroangiodermatitis - Guneet Awal (Our Dermatology Online, 2018)
Stewart Bluefarb syndrome is a rare acroangiodermatitis which occurs due to presence of arteriovenous malformations. It presents at birth or during early childhood as an erythematous to violaceous plaques over the dorsum of foot or ankle. It's a benign condition but can mimic a malignant condition, Kaposi's sarcoma. Histopathological differentiation between these two conditions is important. Investigations like doppler ultrasound are required to establish the diagnosis. In long standing cases, complications like ulceration, bleeding and secondary infections can occur. Treatment includes surgical correction of underlying arteriovenous malformation.